Island of the Blue Dolphins. - O'Dell, Scott, 1898-1989. (Boston, Houghton Mifflin, 1960)
Records the courage and self-reliance of an Indian girl who lived alone for eighteen years on an isolated island off the California coast when her tribe emigrated and she was left behind.
Children's Catalog (Wilson)
Junior High School Library Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
5.5
5-8
Keywords: Survival skills -- Fiction; Newbery Medal books; Indians of North America -- Fiction; Survival -- Fiction; Newbery medal books